2018
DOI: 10.1016/j.ynstr.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Social defeat stress and escalation of cocaine and alcohol consumption: Focus on CRF

Abstract: Both the ostensibly aversive effects of unpredictable episodes of social stress and the intensely rewarding effects of drugs of abuse activate the mesocorticolimbic dopamine systems. Significant neuroadaptations in interacting stress and reward neurocircuitry may underlie the striking connection between stress and substance use disorders. In rodent models, recurring intermittent exposure to social defeat stress appears to produce a distinct profile of neuroadaptations that translates most readily to the reperc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 260 publications
(408 reference statements)
0
38
1
2
Order By: Relevance
“…Por lo tanto la exposición a una DS repetida induciría un incremento prolongado en el tiempo del valor motivacional de la cocaína incrementándose por tanto su potencial de abuso en los sujetos estresados. Nuestros resultados confirman numerosos estudios que han demostrado que la DS en ratones adolescentes y adultos, aumenta los efectos reforzantes de la cocaína utilizando el CPL (Arenas et al, 2016;Montagud-Romero et al, 2016a;Rodríguez-Arias et al, 2015, 2017Ferrer-Pérez et al, 2018a), o la autoadministración de cocaína (Boyson, Miguel, Quadros, DeBold y Miczek, 2011;Holly et al, 2016;Newman, Leonard, Arena, Almeida y Miczek, 2018;Arena, Covington, Herbert, DeBold y Miczek, 2019).…”
Section: Resiliencia Y Susceptibilidad Al Incremento De Los Efectos Runclassified
“…Por lo tanto la exposición a una DS repetida induciría un incremento prolongado en el tiempo del valor motivacional de la cocaína incrementándose por tanto su potencial de abuso en los sujetos estresados. Nuestros resultados confirman numerosos estudios que han demostrado que la DS en ratones adolescentes y adultos, aumenta los efectos reforzantes de la cocaína utilizando el CPL (Arenas et al, 2016;Montagud-Romero et al, 2016a;Rodríguez-Arias et al, 2015, 2017Ferrer-Pérez et al, 2018a), o la autoadministración de cocaína (Boyson, Miguel, Quadros, DeBold y Miczek, 2011;Holly et al, 2016;Newman, Leonard, Arena, Almeida y Miczek, 2018;Arena, Covington, Herbert, DeBold y Miczek, 2019).…”
Section: Resiliencia Y Susceptibilidad Al Incremento De Los Efectos Runclassified
“…A particularly effective social stress model in rodents is the resident-intruder social defeat model in which mice are repeatedly exposed to an unfamiliar, dominant aggressor (Newman et al, 2018) and either socialize with this intruder (where the mice are then dubbed “resilient”) or become anti-social (and are considered more “susceptible” to trauma). This distinction is then used to study biological markers of trauma in the susceptible population.…”
Section: Animal Models Of Ptsdmentioning
confidence: 99%
“…Despite altered activity of the BNST following social defeat, pCREB and pERK expression were unchanged (although perhaps these markers are not activated by social stimuli; Trainor et al, 2011). Finally, intermittent episodes of social stress escalate alcohol and cocaine intake in rats, but continuous exposure attenuates cocaine intake and increases alcohol intake (Newman et al, 2018), a behavioral change that may (like other models of stress-induced reinstatement to drug-seeking; see Miles et al, 2018) be BNST-dependent. Because BNST activity may drive PTSD-like symptomology, neurochemical and anatomical alterations after social defeat stress suggest a critical involvement of BNST in the maintenance and development of PTSD.…”
Section: Animal Models Of Ptsdmentioning
confidence: 99%
“…Brief episodes of aggression from a more aggressive conspecific, together with social subordination, induce anxiety-and depression-like symptoms (Bartolomucci et al, 2009;Nestler and Hyman, 2010;Hollis and Kabbaj, 2014;Czéh et al, 2016;Vannan et al, 2018). Exposure to RSD has also been shown to increase the rewarding effects of drugs of abuse (Ellenbroek et al, 2005;Burke et al, 2011;Aguilar et al, 2013;García-Pardo et al, 2015Newman et al, 2018). Moreover, several studies performed in our laboratory using the conditioned place preference (CPP) paradigm have demonstrated that mice exposed to RSD during late adolescence exhibit an enhanced sensitivity to the rewarding effects of low doses of cocaine in adulthood (Montagud-Romero et al, 2016a,b;Rodríguez-Arias et al, 2017;García-Pardo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%